Direito a educação: politicas publicas para a ressocialização através da educação carcerária na Penitenciária Estadual de Ponta Grossa - Zanin, Joslene Eidam (2008)
The present work has for purpose to delineate a panorama of the current condition of the Brazilian penitentiary system, being about the regeneration function that the education carries out in the politics of penal execution. By means of documental exams and of collection of reports in semi-structured interviews and questionnaires applied to the pedagogic coordination, teachers and arrested pupils on the importance of the pattern of public politics of penitentiary education applied in the State of Paraná, we tried to understand the function that the youths' education and adults, accomplished through Ceebja Odair Pasqualini, school inserted in the State Penitentiary of Ponta Grossa, exercises in the penitentiary system of Parana, presenting and analyzing the relationships among school education and regeneration inserted in a penal system. The theoretical reference used took for base mainly the reflections of Michel Foucault, intending to analyze the politics of prison education developed in the prisons of the State of Paraná in execution to the determination in the article 205 of the Federal Constitution of 1.988 and article 83 of the Law of Penal Execution - Law 7.210 of July 11, 1984, considering as priority the perception that the pedagogic coordination and the teachers possess in relation to that public politics developed by the State; and as the pupils in feather execution in the institution evaluate the education of the which they are part. Before the scarce academic production and of the peculiarity of the theme related to that study area, it is waited that work can collaborate with the research about the prison regeneration and the institution of specific public politics for the education in jail.